Polybrominated diphenyl ethers in surface sediments from fishing ports along the coast of Bohai Sea, China. (March 2021) - Liu, Binxu; Song, Ningning; Jiang, Tao; Wu, Juan; Zhang, Lei; Ge, Wei; Chai, Chao
Abstract: The distribution, congener patterns, possible sources, and ecological risks of polybrominated diphenyl ethers (PBDEs) were investigated in the surface sediments of 20 fishing ports along the coast of Bohai Sea. PBDEs are widespread pollutants in fishing ports, and the total concentrations of 14 PBDEs (∑14 PBDEs) are 4.23–20.59 ng/g with a mean value of 12.56 ng/g. BDE-209 was the dominant congener. The fishing ports with high PBDE concentrations were located near Liaohe River, Haihe River, manufacturing plants of BFRs near Laizhou Bay, and tipping areas of marine garbage. BDE-209 and BDE-47 were the most important congeners that discriminate PBDE pollution. The possible sources of PBDEs included the input of commercial mixtures of penta-BDE, octa-BDE, and deca-BDE, the debromination of BDE-209, and the atmospheric transport of the low brominated diphenyl ethers. The ecological risks in surface sediments were attributed to the congeners of tetra-BDE, penta-BDE, and deca-BDE with low or medium levels. Highlights: Levels of PBDE contamination in fishing ports in Bohai Sea were moderate. Land-based pollutants and fishing vessels played an important role in PBDEs. BDE-209 and BDE-47 were important congeners that discriminate PBDE pollution. Possible sources were commercial mixtures, debromination, atmospheric transport. Risks were attributed to tetra-, penta- and deca-BDEs with low or medium levels.